Reviewing Evidence for the Impact of Lion Farming in South Africa on African Wild Lion Populations - Jennah Green; Angie Elwin; Catherine Jakins; Stephanie-Emmy Klarmann; Louise de Waal; Madeleine Pinkess; Neil D’Cruze (Animals)
The scope and scale of commercial captive lion breeding (CLB) in South Africa have rapidly increased since the 1990s. We conducted a qualitative systematic review using the PRISMA protocol to determine whether CLB provides a sustainable supply side intervention to reduce pressure on wild lion populations. A search was performed using three academic databases for sources published between 2008 and 2023. We collated and reviewed the data using an evaluation framework to determine the potential benefits and threats of CLB in the context of conservation. Among the 126 peer-reviewed and 37 grey literature articles identified, we found evidence suggesting that the framework’s criteria were not fully met, raising concerns that CLB may facilitate the demand for lions, their parts, and derivatives. Our findings further indicate a reasonable cause to doubt that the CLB provides a sustainable supply side intervention to meet the commercial demand for lions, their parts, and derivatives. This could adversely impact conservation of wild lion populations. We conclude that further research is required to effectively evaluate the purported conservation benefits of CLB. These insights may also have implications for the policy and governance of commercial predator breeding operations in South Africa and globally.